2011
DOI: 10.1186/1471-2334-11-75
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalised patients with suspected 2009 H1N1 Influenza A in a hospital in Norway, July - December 2009

Abstract: BackgroundThe main objective of this study was to describe the patients who were hospitalised at Oslo University Hospital Aker during the first wave of pandemic Influenza A (H1N1) in Norway.MethodsClinical data on all patients hospitalised with influenza-like illness from July to the end of November 2009 were collected prospectively. Patients with confirmed H1N1 Influenza A were compared to patients with negative H1N1 tests.Results182 patients were hospitalised with suspected H1N1 Influenza A and 64 (35%) test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
3
12
1
1
Order By: Relevance
“…In agreement with other reports, we found that the incidence of laboratory confirmed cases greatly underestimate the impact of the disease [43]. At the peak of the pandemic, rt-PCR test results were delayed due to overwhelming demand and limited laboratory capacity, resulting in the low number of positive PCR tests.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In agreement with other reports, we found that the incidence of laboratory confirmed cases greatly underestimate the impact of the disease [43]. At the peak of the pandemic, rt-PCR test results were delayed due to overwhelming demand and limited laboratory capacity, resulting in the low number of positive PCR tests.…”
Section: Discussionsupporting
confidence: 77%
“…The clinical findings mirror reports from other countries that fever, dry cough and general malaise were the predominant symptoms upon hospital admission [35,[39][40][41][42][43]. Furthermore, the majority of patients had underlying co-morbidities, most commonly cardiovascular disease.…”
Section: Discussionsupporting
confidence: 65%
“…However, our study showed a relatively low mortality rate compared to previous studies (3.8% versus 6.5%) among patients in these two seasons [23][24][25]. Moreover, noteworthy is the occurrence of relatively frequent severe forms of the disease, including those with fatal outcomes in previously healthy young individuals.…”
Section: Discussioncontrasting
confidence: 71%
“…Some reports suggest that 20%-45% of the deceased patients were younger than 50 years of age and had no previously recorded risk factors [4,[19][20][21]24,26]. In our study, the average age of deceased patients during the pandemic season was 35.3, and most of these patients had some risk factors.…”
Section: Discussionsupporting
confidence: 43%
“…The number of patients that are admitted to an ICU may vary related to criteria used by the institution. Consequently, the mortality in ICU differs has been reported from 11% to 25% 15, 21, 22, 23, 24, 25. Many patients with severe disease have co‐morbidities, but it is well described that fatalities from pandemic influenza may occur in previously healthy subjects.…”
Section: Discussionmentioning
confidence: 99%